STRUKTURALISME DALAM LIRIK LAGU “NOT LIKE THE MOVIE” KATTY PERY - Ulfah Mey Lida (IAIN Bengkulu, 2019)
The song is a work of art that comes from the relationship of sound and language. The purpose of this research is to know the structuralism in Katty Pery's song